FINANCIAL TOOLS AND RISKS RELATED TO THEIR USE BY ECONOMIC ENTITIES IN ROMANIA - ILIE RĂSCOLEAN; ILEANA-SORINA RAKOS (Annals of the University of Petrosani: Economics)
With this article the authors are trying to briefly present the evolution of capital market risks associated with the use of financial instruments by economic entities. Over time, risk assessment methods have evolved, with the aim of providing accurate and timely information to decision-making. Understanding the uncertainty and risks affecting the process deployment helps improve decisions. If, in the 20th century, companies were preoccupied with dominating the economy and stock exchanges, in the 21st century the emphasis was on risk management and assessment in a holistic way. In the current economic context, the success of a business is a problem of adaptation to the environment, and the connection of an economic entity to the economic and social environment is a premise of their functionality. The conceptual evolution between the financial and accounting approach of financial instruments influenced their relationship to their use by economic entities in their elementary preoccupations (investment, financing and exploitation).